2001
DOI: 10.1093/emboj/20.24.7052
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Nedd4-2 by Sgk1 regulates epithelial Na+ channel cell surface expression

Abstract: The epithelial Na(+) channel (ENaC) plays an essential role in the regulation of whole body Na(+) balance and blood pressure. The cell surface expression of this channel, a complex of three subunits (alpha, beta and gamma ENaC), has been shown to be regulated by hormones such as aldosterone and vasopressin and by intracellular signaling, including ubiquitylation and/or phosphorylation. However, the molecular mechanisms involving phosphorylation in the regulation of ENaC are unclear. Here we show by expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
659
2
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 641 publications
(702 citation statements)
references
References 61 publications
39
659
2
2
Order By: Relevance
“…Indeed, glucocorticosteroids have been shown to induce a-ENaC transcription, 57,58 and in human fetal lung explant cultures all three ENaC subunits were upregulated by glucocorticosteroids. 59,60 Glucocorticosteroids also increase the number of available sodium channels by increasing ENaC trafficking and decreasing the rate of degradation of existing channels 61,62 and improving lung responsiveness to b2 stimulants and thyroid hormones. 63 Stutchfield et al 64 have shown that two doses of betamethasone given 48 h before cesarean section significantly decreased admissions due to respiratory distress.…”
Section: Lung Fluid During and Immediately After Birthmentioning
confidence: 99%
“…Indeed, glucocorticosteroids have been shown to induce a-ENaC transcription, 57,58 and in human fetal lung explant cultures all three ENaC subunits were upregulated by glucocorticosteroids. 59,60 Glucocorticosteroids also increase the number of available sodium channels by increasing ENaC trafficking and decreasing the rate of degradation of existing channels 61,62 and improving lung responsiveness to b2 stimulants and thyroid hormones. 63 Stutchfield et al 64 have shown that two doses of betamethasone given 48 h before cesarean section significantly decreased admissions due to respiratory distress.…”
Section: Lung Fluid During and Immediately After Birthmentioning
confidence: 99%
“…This observation has potentially important physiologi-cal ramifications. SGK1, a member of the PKB/Akt family of serine/threonine kinases (20), is an immediate early aldosterone-induced gene product (21,22) in the renal collecting duct (22)(23)(24), which has been shown recently to regulate epithelial Na ϩ channel (ENaC) cell surface expression (25) and, consequently, act as a key mediator of the early aldosterone effect on sodium transport in the distal nephron. Conceivably, SGK1 might also control the number of functional ROMK channels at the plasmalemma and explain how aldosterone regulates renal potassium secretion.…”
Section: From the Department Of Physiology University Of Maryland Scmentioning
confidence: 99%
“…4 In contrast, phosphorylation of NEDD4-2 (neural precursor cell-expressed developmentally downregulated 4-2) inactivates it by preventing the binding to its substrate, ENaC (epithelial sodium channel). 5 In addition, other mechanisms of regulation exist, such as intermolecular and intramolecular interactions. Examples include p19/Arf (alternative reading frame) that binds to mouse double minute (Mdm2) and inhibits p53 conjugation, 6 and the polycomb group (PcG) protein BMI1 that stimulates the histone H2A ubiquitinating activity of RING1B.…”
mentioning
confidence: 99%